Enhancing implementation of information and communication technologies for post-discharge care among hospitalized older adult patients: development of a multifaceted implementation intervention package using the behavior change wheel and implementation research logic model - Dorothy Yingxuan Wang; Eliza Lai-Yi Wong; Annie Wai-Ling Cheung; Zoe Pui-Yee Tam; Kam-Shing Tang; Eng-Kiong Yeoh (Implementation Science Communications)
Abstract Background The integration of information and communication technologies in clinical practice can supplement traditional care pathways on discharge education and has exhibited evident benefits in improving patient health outcomes. However, healthcare providers have reported difficulties in adopting such technologies. The existing evidence on implementation interventions supporting the implementation of information and communication technologies is insufficient, characterized by infrequent utilization or reporting of implementation theories in implementation intervention designs. This study aims to outline the creation of a theory-informed implementation intervention package to enhance the clinical implementation of information and communication technologies for post-discharge self-care among hospitalized older adults. Methods This study systematically applies the Behavior Change Wheel (BCW) approach, involving behavior diagnosis, identification of intervention options, and intervention content selection, informed by conceptual frameworks, empirical data, and relevant literature. Additionally, the Implementation Research Logic Model is utilized to synthesize, organize, and visually present the collected data. Results This structured process identified and selected five intervention functions, 11 behavior change techniques, and four policy categories. A multifaceted implementation intervention package was developed, containing four components: (i) flexible and sustainable training, (ii) mass media and opinion leader campaign, (iii) technology and workflow redesign, and (iv) regular corporate-level audit and feedback. Conclusions The study addresses the incomplete evidence base for implementation interventions supporting clinical information and communication technology implementation, presenting a practical, evaluable, and scalable theory-informed implementation intervention package. By providing an example of the application of the BCW approach and logic model, this study contributes to the knowledge on implementation intervention design, offering valuable insights for researchers and practitioners aiming to improve healthcare providers' behavior change and post-discharge care management with technology-based interventions.